2022
DOI: 10.3390/ijms231911555
|View full text |Cite
|
Sign up to set email alerts
|

Naked and Decorated Nanoparticles Containing H2S-Releasing Doxorubicin: Preparation, Characterization and Assessment of Their Antitumoral Efficiency on Various Resistant Tumor Cells

Abstract: Several semisynthetic, low-cardiotoxicity doxorubicin (DOXO) conjugated have been extensively described, considering the risk of cytotoxicity loss against resistant tumor cells, which mainly present drug efflux capacity. Doxorubicin 14-[4-(4-phenyl-5-thioxo-5H-[1,2]dithiol-3-yl)]-benzoate (H2S-DOXO) was synthetized and tested for its ability to overcome drug resistance with good intracellular accumulation. In this paper, we present a formulation study aimed to develop naked and decorated H2S-DOXO-loaded lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Despite this, several investigations have revealed that OS patients may innately resist DOXO due to ATP-binding cassette transporter-mediated drug efflux [57,58]. Hence, the formulation and testing of naked and decorated H 2 S-DOXO-loaded lipid NPs against various cells, including DOXO-resistant human/mouse OS cells (U-2OS/DX580/K7M2), have elicited the inter-cellular drug delivery and increased cytotoxic effect towards resistant cells [59]. The manipulation through surface modifications, particularly with PEG, resulted in the controlled delivery of active ingredients from DOXO for an extended period [60].…”
Section: Organic Nanocarriersmentioning
confidence: 99%
“…Despite this, several investigations have revealed that OS patients may innately resist DOXO due to ATP-binding cassette transporter-mediated drug efflux [57,58]. Hence, the formulation and testing of naked and decorated H 2 S-DOXO-loaded lipid NPs against various cells, including DOXO-resistant human/mouse OS cells (U-2OS/DX580/K7M2), have elicited the inter-cellular drug delivery and increased cytotoxic effect towards resistant cells [59]. The manipulation through surface modifications, particularly with PEG, resulted in the controlled delivery of active ingredients from DOXO for an extended period [60].…”
Section: Organic Nanocarriersmentioning
confidence: 99%
“…In recent years, various nanoformulations such as inorganic nanoparticles (NPs) (Li et al., 2020 ), liposomes (Jing et al., 2022 ), nanogel (Zhang et al., 2018 ), lipid NPs (Peira et al., 2022 ), and polymeric NPs (Heyder et al., 2021 ) had been widely exploited for targeting treatment of osteosarcoma (Ambrosio et al., 2021 ; Wu et al., 2022 ). Nanoformulations can target and deliver therapeutics to osteosarcoma region to improve therapeutic benefits and decrease adverse effects of therapeutics (Jo et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reaching a therapeutic outcome that is able to fight neurodegenerative disorders, tumoral diseases, or immunological disorders is facilitated by an efficient and site-specific delivery of compounds. For these reasons, this Special Issue collates different aspects of research into nanotechnology in order to identify new therapeutic targets and strategies, including review papers [4,5], mathematical models to calculate the trajectories of magnetic NPs in the body or clarify the structures of metal-decorated fullerenes [6,7], the drug delivery systems of different antitumoral agents [8][9][10][11], and the biocompatibilities of stealth liposomes and hybrid nanosystems containing surfactant agents [12,13].…”
mentioning
confidence: 99%